2019
DOI: 10.1177/0300060519833529
|View full text |Cite
|
Sign up to set email alerts
|

A case of varicella zoster encephalitis with glossopharyngeal and vagus nerve injury as primary manifestation combined with medulla lesion

Abstract: Varicella zoster virus (VZV) can invade the brainstem or brain via the glossopharyngeal, vagus , or facial nerve, resulting in brainstem inflammation or encephalitis. We report the case of a 66-year-old male patient with a primary manifestation of medulla injury of the glossopharyngeal and vagus nerves, combined with a medulla lesion, who was misdiagnosed with lateral medullary syndrome. Facial nerve injury and earache subsequently occurred and human herpes virus 3 (VZV) was detected by second-generation seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…In one case, diffusion restriction in the lateral medulla on MRI in a patient with dysphagia and dysarthria suggested an infectious process and this patient later developed Ramsey Hunt syndrome. 6 In another case, a patient presented with a laryngeal mass that was concerning for cancer, similar to our patient, however the mass persisted and was biopsied revealing general-inflammatory changes. This patient also developed facial paralysis helping to confirm the final diagnosis.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In one case, diffusion restriction in the lateral medulla on MRI in a patient with dysphagia and dysarthria suggested an infectious process and this patient later developed Ramsey Hunt syndrome. 6 In another case, a patient presented with a laryngeal mass that was concerning for cancer, similar to our patient, however the mass persisted and was biopsied revealing general-inflammatory changes. This patient also developed facial paralysis helping to confirm the final diagnosis.…”
Section: Discussionsupporting
confidence: 73%
“…It is postulated that retrograde transmission from the pharyngeal mucosa through the vagal and glossopharyngeal nerves to the medulla is the mechanism for VZV spread in this case. 5,6 It seems possible that the mass originally seen in our patient, like the mass seen in the case of Choi, was an area of acute inflammation that may have served as a nidus for the virus to infect the nerves. Neuroinvasive VZV is clinically heterogenous and therefore may be difficult to diagnose.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We later diagnosed our patient with PRES secondary to Varicella encephalitis based on the detection of VZV DNA in CSF using PCR. Cao et al reported a case of Varicella encephalitis presenting as a lateral medullary syndrome [ 9 ]. However, to the best of our knowledge, Varicella encephalitis with clinical and radiological findings consistent with PRES has never been described in the literature before.…”
Section: Discussionmentioning
confidence: 99%
“…However, invasion of the vagus nerve by VZV is very rare. Cao et al 1 reported a case of VZV encephalitis with glossopharyngeal and vagus nerve injury as the primary manifestation combined with a medulla lesion. In that case, the patient exhibited dysphagia and a hoarse voice and was misdiagnosed with lateral medullary syndrome.…”
Section: Introductionmentioning
confidence: 99%